An empirical analysis of Brazilian courts law documents using learning techniques - Silva, Bruno; da Costa-Abreu, Marjory (Anais do Workshop de Forense Computacional, 2019)
This paper describes a survey on investigating judicial data to ﬁnd patterns and relations between crime attributes and corresponding decisions made by courts, aiming to ﬁnd import directions that interpretation of the law might be taking. We have developed an initial methodology and experimentation to look for behaviour patterns to build judicial sentences in the scope of Brazilian criminal courts and achieved results related to important trends in decision making. Neural networks-based techniques were applied for classiﬁcation and pattern recognition, based on Multi-Layer Perceptron and Radial-basis Functions, associated with data organisation techniques and behavioral modalities extraction.